Lexical Hedges Used by the Female Characters in Birds of Prey Movie - Ira Yunita, Ni Nyoman Ayu Mas; Puspani, Ida Ayu Made; Adni, Nissa Puspitaning (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
This study was entitled Lexical Hedges Used by The Female Characters in Birds of Prey Movie. This study aimed to figure out the lexicons used as lexical hedges and analyzed why those were used in Birds of Prey movie. The data was collected from the utterances of the female characters in the 2020 movie Birds of Prey, directed by Cathy Yan. The data was collected through documentation and note-taking method. In analyzing the data, descriptive qualitative method was applied based on Lakoff's (1975) theory of lexical hedges. The result of the analysis showed several examples of types of lexicons as lexical hedges used by the female characters, including “well,” “you know,” “I think,” “I guess.” For the used of lexical hedges in Birds of Prey, demonstrating their preference for employing these linguistic strategies to convey uncertainty, weaken assertions, and enhance politeness in their interactions. Keywords: Sociolinguistics, Women’s Language Features, Lexical Hedges